2017
DOI: 10.1007/s12272-017-0927-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of FSLLRY-NH2 on inflammatory responses induced by hydrogen peroxide in HepG2 cells

Abstract: Proteinase activated receptor 2 (PAR2), which is localized in the GI tract, the respiratory system, and the kidney tubules is a G protein-coupled receptor associated with inflammation, metabolism, and disease. The aim of this study was to explore the role of PAR2 in hydrogen peroxide (HO)-induced HepG2 cells by using FSLLRY-NH a PAR2 antagonist. HO treatment resulted in induction of PAR2 in esophageal, gastric, and liver cells, with the most robust response being in HepG2 cells. Furthermore, this effect was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…H 2 O 2 can react with cellular Fe 3+ through the Fenton reaction and produce highly reactive oxygen species (ROS). Excessive ROS stimulation leads to oxidative stress in cells, where the generated ROS attacks the unsaturated fatty acids in the phospholipid membrane, triggering a cascade of lipid peroxidation reactions ( 17 ). Therefore, this study employed hydrogen peroxide to induce oxidative damage in the cell model.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 can react with cellular Fe 3+ through the Fenton reaction and produce highly reactive oxygen species (ROS). Excessive ROS stimulation leads to oxidative stress in cells, where the generated ROS attacks the unsaturated fatty acids in the phospholipid membrane, triggering a cascade of lipid peroxidation reactions ( 17 ). Therefore, this study employed hydrogen peroxide to induce oxidative damage in the cell model.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress plays an important role, especially in the initiation and progression of hepatic damage in inflammatory liver diseases such as ALD. An enzyme-dependent antioxidant system plays a crucial role in ROS-associated liver damage (Ai et al 2013;Jang et al 2017a;Lee et al 2017). Chronic alcohol consumption causes an imbalance between ROS production and elimination, impairing antioxidant capacity in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…CAT plays an important role in reducing free radicals and preventing oxidative stress in stagnant bile acids. In measurements of CAT activity, MBDL surgery reduced CAT levels, which caused oxidative stress [3738]. Restoration of CAT levels by administration of NaHS indicated that NaHS reduced oxidative stress by MBDL and ameliorated liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%